Hydrocarbon Evaluation and New Well Prognosis Based on Seismic and Petrophysical Analysis of Ghauspur Area, Central Indus Basin, Pakistan - Shakir, U.; Ali, M.; Hussain, M.; Fahd, M.; Abuzar, M.K.; Khan, M.A.; Amjad, M.R.; Siyar, S.M.; Tahir, A.R. (The Nucleus, 2017)
Reservoirs are characterized by significant heterogeneity at numerous scales ranging from exploration to production and enhanced production scale. The variations of primary depositional facies could be identified using seismic and well log data as it controls the architecture of a reservoir. Seismic data helps in accurate reservoir characterization. The present research is based upon 2D seismic interpretation, attribute and petrophysical analysis of Ghauspur area, Central Indus Basin, Pakistan. Interpretation of seismic lines shows negative flower structure bounded by two normal faults dipping in the northwest (NW) to southeast (SE) direction. Attribute analysis improved geologic visualization and shows the presence of hydrocarbons at well Indus-1B because of low frequency and low amplitude values. Petrophysical characterization of Sui Main Limestone (SML) penetrated in Indus-1B and Badar South-01 wells was evaluated which proved it to be water-wet with no economic potential for hydrocarbons. On the basis of seismic data interpretation, attribute and petrophysical analyses, a new well location is proposed on the crustal part of the structure.